2021
DOI: 10.1094/pdis-01-21-0179-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Grapevine Virus H in Grapevine in Greece

Abstract: Grapevine virus H (GVH) is a member of the genus Vitivirus in the family Betaflexiviridae (subfamily Trivirinae, order Tymovirales) that infects grapevine (Candresse et al., 2018). GVH was first identified in a symptomless grapevine of an unknown cultivar from Portugal in 2018 (Candresse et al. 2018), and since then the virus has been reported only from California (Diaz‑Lara et al. 2019). Several vitiviruses have been detected in Greek vineyards (Avgelis and Roubos 2000; Dovas and Katis 2003a; 2003b; Panailido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…GVH (Grapevine virus H) is a member of the genus Vitivirus; it was first detected in an asymptomatic sample of an unknown grapevine cultivar from Portugal [94]. GVH has been identified in Greece [95], Croatia [96], and in California in collection samples of NCGR [81]. As a result of RNA-seq and the bioinformatics analyses, we identified reads mapping to GVH in three samples (N12, N28, N36).…”
Section: Family: Betaflexiviridaementioning
confidence: 98%
“…GVH (Grapevine virus H) is a member of the genus Vitivirus; it was first detected in an asymptomatic sample of an unknown grapevine cultivar from Portugal [94]. GVH has been identified in Greece [95], Croatia [96], and in California in collection samples of NCGR [81]. As a result of RNA-seq and the bioinformatics analyses, we identified reads mapping to GVH in three samples (N12, N28, N36).…”
Section: Family: Betaflexiviridaementioning
confidence: 98%
“…The present study documents the occurrence of GVH in Croatian autochthonous grapevine cultivars as the eighth vitivirus confirmed in Croatia. After the discovery of GVH in a symptomless grapevine of an unknown cultivar in Portugal [11], in several cultivars at the USDA National Clonal Germplasm Repository (NCGR) in Winters [36], and recently in commercial vineyards in the cultivar Assyrtiko in Greece [37], this study extends the information on the GVH geographic distribution. Like the NCGR results, where…”
Section: Discussionmentioning
confidence: 65%
“…The present study documents the occurrence of GVH in Croatian autochthonous grapevine cultivars as the eighth vitivirus confirmed in Croatia. After the discovery of GVH in a symptomless grapevine of an unknown cultivar in Portugal [11], in several cultivars at the USDA National Clonal Germplasm Repository (NCGR) in Winters [36], and recently in commercial vineyards in the cultivar Assyrtiko in Greece [37], this study extends the information on the GVH geographic distribution. Like the NCGR results, where GVH was confirmed in different cultivars from different viticultural regions, a similar situation was found in this study, as GVH was confirmed in cultivars mainly originating from three different sites located in the coastal part of Croatia with a Mediterranean climate (Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 65%
“…In the past few years, several vitiviruses, namely GVA, GVB, GVE, GVF, GVI, and GVH, have been reported in Greek vineyards [20][21][22][23][24][25]. In this study, GVL was initially identified using high-throughput sequencing (HTS), and a broader survey was then conducted to determine the diversity and phylogenetic relationships among populations.…”
mentioning
confidence: 99%
“…Greece is the tenth country in which GVL has been detected, after Canada, Croatia, New Zealand, the USA [3,13,14], Tunisia [15], Turkey [16], South Africa [17], Korea [18], and France [19]. In addition, the identification of GVL has increased the number of vitiviruses that are known to be endemic in Greek vineyards to seven [20][21][22][23][24][25].…”
mentioning
confidence: 99%